REPRESENTASI PORNOGRAFI PADA MEDIA SOSIAL (ANALISIS SEMIOTIKA PIERCE PADA APLIKASI BIGO LIVE) - Sultan Himawan (MediaKom : Jurnal Ilmiah Komunikasi, 2018)
The purpose of this study is to find and describe the form of pornography that occurs on social media Bigo Live and the meaning of symbols and symbols of communication used in the application. The results of this study can be understood that the symbol of communication used in semiotics pierce, consisting of icons, indices and symbols komuniksi on Bigo Live indicated the existence of pornography because it contains objects that lead to sexual activity. Behind this it turns out there are economic interests of the people involved in Bigo Live including the company Bigo Live itself. However, the viewers or known as the viewer tend to be lovers who are willing to spend the money in order to give a gift in this form of index to the hosts who are broadcasting to apply sexy clothes or gestures. Seeing the conditions of these elements, the social reality of Bigo Live produces culture. This is because the process of interaction that takes place between users and the technology that enumerates the user structure at Bigo Live in a particular time and location will result in a culture. Therefore, text or content becomes cultural artifacts. As cultural artifacts, content becomes a reference to see how cyber culture is shaped, exchanged, and even consumed by users at Bigo Live. Keywords: Pornography, Symbol of Communication, Social Media Communication